The Conception of History in Velleius Paterculus' Historia Romana - Domainko, Annika (Histos, 2015)
This article explores the conception of history in Velleius Paterculus’ historiography. It argues that this conception is, against common assumptions, by no means one-dimensional court propaganda, but the result of a subtle tension between teleology and unpredictability arising from Tiberian Rome. Approaching Velleius’ History from this perspective allows us to deepen our understanding of both the significance of history under Tiberius and the anthropological function and value of (historiographical) narrative as a means of coming to terms with the exposure of human life.